Interleukin 15 - biological properties and antitumor activity - Mackiewicz, Jacek; Kasperkiewicz, Michał (Contemporary Oncology/Współczesna Onkologia, 2002)
IL-15 and IL-2 demonstrate similar biologic properties in vitro. They share a receptor component (IL-2/15 βγ(c)) but have an unique specific a chain, which completes IL-αβγ and IL-2Rαβγ. The mechanism of signal transduction of these two cytokines is similar. IL-15 plays an essential role in the development of NK cells. Like IL-2, it activates antibody-dependent cellular cytotoxicity (ADCC). IL-15 stimulates NK cell cytokine and chemokine production [ (MIP)-1 α and β, INF-γ, GM-CSF], which is in- creased with the co-stimulation of IL-12. The effect of combination of IL-15 and IL-12 on NK cells can be compared to IL-18 + IL-12. Monocytes/makrophages and granulocytes demonstrate an expression of high affinity to IL-15R. IL-15 has also an influence on TCR αβ. It directs monocyte differentiation into dendritic cells with features of Langerhans cells. IL-15 bears a potential for clinical application in tumour immunotherapy. The IL-15 administration causes the expansion of NK cells, CD8+ cells and other non-classical subpopulations of T cells. Apoptosis caused by endothelial and tumour cells is essentially lower after the simulation with IL-15 than stimulation IL-2. IL-15 has also a beneficial influence on the restoration of cytokine type 1 and type 2 balance. IL-15 stimulates activity against many types of tumours, by activation of CD8+, NK cells, chemokines and cytokines. IL-15 also plays a role in the pathogenesis in various diseases including tumours. IL-15 can also be useful as an adjuvant in anti-tumour vaccines.